Donacije Janeza Nepomuka Kalistra - tržaškega "self-made mana" - in njegove vdove Marije v meščanski kulturi darovanja - Čeč, Dragica (Annales. Series historia et sociologia, 2023)
In the 19th century, political theory promoted the institutionalisation and systematisation of social issues. While it created the first systems for addressing social issues, it was rather (un)successful in establishing the systemic resources for their operation. Thus, the implementation of systemic responses to social issues has often been based on mutual solidarity in the so-called »mixed economy of welfare«. As a rule, the ‘donors’ cover areas of social issues that are prioritised by bourgeois society and the bureaucracy. Bourgeois society in general neglected rural areas, which bore the brunt of the early economic crisis, which was covered by large tax increases and land alienation, and with s. c. »Heimarrecht« (1863) was also predicted to take the lion’s share of the social care of disabled migrant workers without property. An analysis and evaluation of the donations of John Nepomuk Kalister and his wife/widow Maria Kalister raises the question of motives for personal giving and personal responsibility in a culture of giving as the foundations on which the »mixed economy of welfare« was based. The article will specifically address the interplay of centuries-old moral and other motives and practices of giving with new, Enlightenment ones, which are also reflected in the donations and bequests of John Nepomuk Kalister.
Keywords: aree rurali; beneficienza; bourgeois morality; charity; compassion; compassione; countryside; dobrodelnost; Družbeni problemi; Humanitarnost; Janez Kalister; Marija Kalister; meščanska morala; mixed economy of welfare; Morala; morale borghese; podeželje; questioni sociali; social issues; Socialno skrbstvo; Sočutje; Srednji razred; Trieste; welfare policies; Zgodovina